Docosahexaenoic Acid Conjugation Enhances Distribution and Safety of siRNA upon Local Administration in Mouse Brain - Mehran Nikan; Maire F Osborn; Andrew H Coles; Bruno MDC Godinho; Lauren M Hall; Reka A Haraszti; Matthew R Hassler; Dimas Echeverria; Neil Aronin; Anastasia Khvorova (Molecular Therapy: Nucleic Acids, 2016)
The use of siRNA-based therapies for the treatment of neurodegenerative disease requires efficient, nontoxic distribution to the affected brain parenchyma, notably the striatum and cortex. Here, we describe the synthesis and activity of a fully chemically modified siRNA that is directly conjugated to docosahexaenoic acid (DHA), the most abundant polyunsaturated fatty acid in the mammalian brain. DHA conjugation enables enhanced siRNA retention throughout both the ipsilateral striatum and cortex following a single, intrastriatal injection (ranging from 6–60 μg). Within these tissues, DHA conjugation promotes internalization by both neurons and astrocytes. We demonstrate efficient and specific silencing of Huntingtin mRNA expression in both the ipsilateral striatum (up to 73%) and cortex (up to 51%) after 1 week. Moreover, following a bilateral intrastriatal injection (60 μg), we achieve up to 80% silencing of a secondary target, Cyclophilin B, at both the mRNA and protein level. Importantly, DHA-hsiRNAs do not induce neural cell death or measurable innate immune activation following administration of concentrations over 20 times above the efficacious dose. Thus, DHA conjugation is a novel strategy for improving siRNA activity in mouse brain, with potential to act as a new therapeutic platform for the treatment of neurodegenerative disorders.